The impact of organizational stress on financial performance: Evidence from software development companies - Shyamali Satpathy; Violeta Cvetkoska; Gokulananda Patel (SPOUDAI - Journal of Economics and Business, 2021)
The aim of this paper is to examine the impact of organizational stress on financial performance in Indian software development companies. A questionnaire was distributed to employees of 17 Indian software development companies and filled by 501. We identified constructs using a literature review and expert opinion, which were then confirmed using exploratory and confirmatory factor analysis. Four stressors are used in this study: job insecurity, work-overload, technological complexity, and technological uncertainty. In the instance of software development companies in India, our findings indicate that stress has no effect on profitability (profit per asset) and vice versa. Additionally, work overload contributes to complexity and job insecurity. Profit orientation drives techno-complexity, while techno-uncertainty is driven by techno-complexity. We discovered that age is the key demographic influencer affecting stress positively and that when the average age exceeds 28 years, the average stress level increases by 15.6 units. This study can assist managers at software development companies in making fact-based decisions about the stressors identified and so foster a more productive work environment.
Keywords: C38; C83; M15; 330; organizational stress; financial performance; stressors; causality; software development companies